Réinterroger les proximités à l’échelle des habitants d’une petite ville périurbaine. Le cas de Saint-Jean-de-Liversay, une commune du rétro-littoral de la façade atlantique. - Elodie Texier; Christophe Demazière (GéoProximitéS)
Research on small or medium-sized towns seems to have found a new impetus since the recent sanitary and social crises. However, the uniqueness of these places makes them difficult to understand. When it comes to small towns in the orbit of large conurbations, collective representations are often torn between an imaginary that is both attractive and repulsive. Residents of such places have long illustrated this paradox, settling there both by default as an area of social relegation, and by choice, stimulated in particular by the cost and availability of land. What is the situation today? Have the reasons for moving to the suburbs changed? More generally, what is the relationship of the inhabitants with proximity? In the first part of this article, we analyse the development issues facing peri-urban towns, based on the residential attractiveness of western France. The second part will be devoted to the empirical results of research into the municipality of Saint-Jean-de-Liversay, located near the La Rochelle conurbation in Charente-Maritime. We will report on a study aimed at gaining a better understanding of the spatial practices of residents and their needs with regard to the town centre. The study combined the results of interviews with residents, a questionnaire survey and a collective spatial reconstruction workshop.